Rhodium-Catalyzed Enantioselective Synthesis of Highly Fluorescent and CPL-Active Dispiroindeno[2,1-c]fluorenes - Cadart, Timothée; Nečas, David; Kaiser, Reinhard P; Favereau, Ludovic; Císařová, Ivana; Gyepes, Róbert; Hodačová, Jana; Kalíková, Květa; Bednárová, Lucie; Crassous, Jeanne; Kotora, Martin (Chemistry (Weinheim an der Bergstrasse, Germany), 2021)
The enantioselective synthesis of chiral [7]-helical dispirodihydro[2,1-c]indenofluorenes (DSF-IFs) was achieved for the first time in good yields with high er values (er up to 99 : 1). The crucial step of the whole reaction sequence was the enantioselective intramolecular [2+2+2] cycloaddition of tethered triynediols to indenofluorenediols, which was catalyzed by a Rh/SEGPHOS® complex. Further transformations led to the corresponding DSF-IFs. The prepared helically chiral DSF-IFs combine circularly polarized luminescence (CPL) activity (glum =∼10-3 ) with exceptionally high fluorescence quantum yields (up to Φlum =0.97).
Keywords: rhodium; Luminescence; helical compounds; stereoizomerie; circularly polarized luminescence; enantioselective cyclotrimerization; fluoreny; Catalysis; catalysis; indenofluorene; luminiscence; katalýza; Rhodium; Fluorenes; Stereoisomerism